Investigating residents’ perception on the quality of life in Wangsa Maju area of Kuala Lumpur City, Malaysia - Mohit, Mohammad Abdul; Hj. Mohd. Noor, Norzailawati; Zahari, Rustam Khairi; Abdul Malek, Nurhayati (2016)
Based on the new Malaysian Wellbeing Index (MWI, 2013) which replaced the earlier Malaysian Quality of Life Index (MQLI), the well-being of Malaysians has improved by 25.4 points in the last 12 years (2000-2012). While Mercer’s quality of living (2015) ranked Kuala Lumpur 84 out of 230 cities; however, these indexes do not match the quality of urban life at the city level, and there is a need to investigate the quality of life of the residents of Kuala Lumpur city that intends to become A World Class City by 2020. Therefore, investigating the quality of City life of Kuala Lumpur requires working at neighborhood level that is the major determinant of the overall quality of life of the city. With this background, the main purpose of the study was to investigate residents’ perception on both subjective and objective qualities of life within the living environment of Wangsa Maju area of Kuala Lumpur City. Based on an intensive literature survey, a questionnaire was designed with seven domains/ components of QOL framework. The questionnaire survey was conducted on a sample of 200 residents. The findings suggest that the residents are not satisfied with their economic condition and the safety condition that prevail in the area. However, they are a little over slightly satisfied about their housing condition, functional environment, and social and community participation. Although concerning spiritual life residents are nearly satisfied, however, on the physical and emotional health condition, residents appear to be moderately satisfied. The overall findings of the study suggest that the variables of the five components in which the residents have expressed their dissatisfaction or lower level of satisfaction should be improved to enhance the quality of life of Wangsa Maju residents